“Jeune Israël”: Multiple Modernities of Jewish Childhood and Youth in Morocco in the First Half of the Twentieth Century - Guedj, David (The Jewish quarterly review, 2022)
This essay offers a new perspective on childhood and youth in Morocco and western Algeria beginning in the last decades of the nineteenth century. Since most current studies of childhood and youth in that era focus mainly on Europe, and very seldom on Asia and Africa, our knowledge of the latter is limited, particularly with respect to the Jewish communities of Muslim lands as opposed to those of Europe. Furthermore, existing research has relied on texts authored by adults which normally depict childhood solely in the context of the Jewish calendar and Jewish life cycle, but ignores the political, social, and cultural processes set in motion during the mid-nineteenth century which precipitated changes across North Africa with a bearing on children and youth. Based on a review of French texts written by youth in Morocco and western Algeria during the early 1930s and published in a Morocco-based Jewish newspaper, I propose a model of multiple modernities in Jewish childhood and youth throughout the region. The model comprises a variety of programs: the adoption of modern European ideals, educational values, and leisure culture; the emergence of a modern national Jewish identity, Hebrew and Zionist; the continued observance of family and community traditions; and finally, the cultural segregation of Jewish youth from the surrounding population.